Studi Eksplorasi Stres Pada Mahasiswa Di Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung Semarang - Girang Tri Lumintu; Moch Aspihan; Iskim Luthfa (Journal of Health, Medical, and Psychological Studies, 2025)
Nursing students constitute a population that is particularly vulnerable to stress due to academic demands, clinical practice requirements, and complex psychosocial pressures. Poorly managed stress may adversely affect mental health, learning motivation, and academic performance. This study aimed to explore the levels of stress among students of the Faculty of Nursing at Sultan Agung Islamic University, Semarang. A descriptive study design with an exploratory quantitative approach was employed. The sample consisted of active students selected using purposive sampling techniques. Data were collected using a stress-level questionnaire that had been tested for validity and reliability. Univariate analysis was conducted to describe the frequency distribution of respondents’ stress levels. The findings revealed that the majority of students experienced moderate stress, followed by mild and severe stress. Academic factors, workload, clinical practice demands, and time pressure were identified as the main contributors to stress. These results highlight the crucial role of educational institutions in providing psychological support programs and promoting adaptive coping strategies to enhance student well-being and support academic success.